Changes in Attitudes of Annelies in the Film “Bumi Manusia” by Hanung Bramantyo” - Bismil Tirta Jalisman (Cinematology: Journal Anthology of Film and Television Studies, 2021)
Film as an art of moving images, intellectually, humans can see an event more real. Through film shows, each scene can be more easily read and understood because through the senses of the human eye it is directed to one scene perception. This study discusses changes in the attitude of the main character in the human world, namely Annalies. The problem discussed in this study is the change in the attitude of the main character in the film "Bumi Manusia" by Hanung Bramantyo. The aim is to find and describe changes in attitudes, especially in the Annelies cast. This qualitative descriptive research uses content analysis techniques related to semiotics, with data sourced from films. The results showed: 1) Annelies, who originally loved her native land, had to leave and go to the Netherlands; 2) Annelies, who originally loved her husband Minke, had to leave Minke to go to the Netherlands, and 3) Annelies, who originally had a close relationship with her mother, Nyai Ontosoroh, had to leave her and go to Holland. The implications of this research can be a reference for filmists in seeing visual meanings to capture messages more deeply.